In the Meantime: RE/UN/DIScover Heuristic for Small-Scale Antioppressive Action within Systems and Organizations - Keenan, Elizabeth King (Social Work, 2023)
The dehumanizing effects of neoliberal, white dominant regulations, laws, policies, and cultural assumptions seep into the everyday practice of social workers in frontline and mid-level positions. Many social workers are learning various antioppressive practices and becoming aware of how microaggressions and other oppressive dynamics can manifest in workplaces but lack models to guide efforts for small-scale action. This article describes how the RE/UN/DIScover heuristic can be used to interrupt and shift oppressive processes during everyday moments of practice within organizations and systems by social workers and their interested colleagues who have some awareness of oppressive and antioppressive dynamics. The RE/UN/DIScover heuristic is an iterative set of three practices: (1) tend to self with compassionate REcover practices; (2) engage in curious, critical reflection to UNcover full understandings of the power dynamics, impacts, and meanings of specific challenges; and (3) DIScover and try out just, humanizing responses with creative courage, individually and with other colleagues. The heuristic uses a dual focus on self and situation with an ad hoc group of other colleagues to raise awareness; cultivate humanizing spaces; and implement antioppressive, relational responses. The article describes the heuristic practices and how to apply the heuristic with two composite practice applications.
Keywords: dept.swk; peer-reviewed